Hubungan Pemahaman Materi Thaharah dengan Kebiasaan Perilaku Hidup Bersih dan Sehat (PHBS) pada Siswa di MTs Darul Muttaqien, Bogor - Ilma Sabila; Mae’munah Sa’diyah (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2021)
Thaharah is one of the syariah in Islam which teaches its adherents about cleanliness as a form of obedience to the provisions that Allah has commanded. PHBS is a movement, attitude, knowledge, and pro-active action whose aim to maintain and prevent from disease. This study aims to determine the relationship between understanding thaharah material and hygiene and healthy living habits (PHBS). The research method used in this research is correlational quantitative method. The sample in this study were students of class VIII MTs Darul Muttaqien Bogor Regency. The data collection techniques used in this study were questionnaires and tests. The instruments used in this study were 15 test items and 13 questionnaires. The results of the study through correlational tests showed that there was a significant relationship between understanding thaharah material and clean and healthy living habits (PHBS). The correlational test shows a significance value of sig. (2-tailed) 0.0000 <0.05 with a Pearson correlation value of 0.878 so that it is interpreted that the relationship between the two is strong